A framework for identifying mathematical arguments as supported claims created in day-to-day classroom interactions - Nordin, Anna-Karin; Björklund Boistrup, Lisa (The Journal of mathematical behavior, 2018)
•Innovative framework with mathematical arguments reconstructed as supported claims.•Arguments expressed in many ways (including e.g., drawings) allowing for also informal arguments to be identified.•Findings suitable to adopt in further research and professional development projects.•Framework constitutes a basis for studies on classroom communication. This article addresses how to distinguish mathematical arguments created during whole class discussions in grades 3–5 in Sweden, while taking a broad range of communicational resources, such as speech, drawings and symbols, into account. We present a step-by-step framework of how to systematically reconstruct mathematical arguments. The framework is developed drawing on Toulmin’s model of argumentation and a multimodal approach. When giving account for the framework, we show how various communicational resources convey the mathematical meaning of the arguments created. The framework can be used for further research investigating interaction in classroom settings, for teacher students as a basis for reflection during practicum periods, as well as a lens for teachers in identifying informal and formal mathematical arguments in day-to-day communication in the mathematics classroom.